ASSESSING STUDENT LEARNING WITH AUTOMATED TEXT PROCESSING TECHNIQUES - Wu, Yi-fang Brook; Chen, Xin (Online Learning, 2005)
Research on distance learning and computer-aided grading has been developed in parallel. Little work has been done in the past to join the two areas to solve the problem of automated learning assessment in virtual classrooms. This paper presents a model for learning assessment using an automated text processing technique to analyze class messages with an emphasis on course topics produced in an online class. It is suggested that students should be evaluated on many dimensions, including the learning artifacts such as course work submitted and class participation. Taking all these grading criteria into consideration, we design a model which combines three grading factors: the quality of course work, the quantity of efforts, and the activeness of participation, for evaluating the performance of students in the class. These three main items are measured on the basis of keyword contribution, message length, and message count, and a score is derived from the class messages to evaluate students’ performance. An assessment model is then constructed from these three measures to compute a performance indicator score for each student. The experiment shows that there is a high correlation between the performance indicator scores and the actual grades assigned by instructors. The rank orders of students by performance indicator scores and by the actual grades are highly correlated as well. Evidence from the experiment shows that the computer grader can be a great supplementary teaching and grading tool for distance learning instructors.